Idiopathic pulmonary hemosiderosis associated with Kabuki syndrome - Yoji Uejima; Kenji Yoshida; Hirofumi Ohashi (Immunological Medicine)
Kabuki syndrome (KS) is a genetic disorder caused by gene mutations in either lysine-specific methyltransferase 2D (KMT2D) or lysine demethylase 6A (KDM6A). This congenital disorder exhibits characteristic facial features, developmental delays in psychomotor skills, and skeletal abnormalities. Moreover, it is classified as a congenital immunodeficient disorder under the category of combined immunodeficiency, leading to hypogammaglobulinemia and the onset of autoimmune diseases. Here, we present the first case of KS complicated by idiopathic pulmonary hemosiderosis (IPH). The KS patient, a 2-year-old Japanese girl with a history of hypoplastic left heart syndrome and recurrent bacterial infection, developed severe respiratory distress and anemia. She had autoimmune hemolytic anemia and gouty nephropathy. Hemophagocytic macrophages with hemosiderin ingestion were identified in bronchoalveolar lavage fluid, excluding differential diagnoses and leading to the diagnosis of idiopathic pulmonary hemosiderosis. Intravenous prednisolone (2 mg/kg/day) was administered, but symptoms did not improve. However, pulmonary hemorrhage disappeared with methylprednisolone pulse therapy. IPH warrants consideration in cases where individuals with KS manifest idiopathic pneumonia and concurrent anemia.